Residual physiological abnormalities after pulmonary endarterectomy and balloon pulmonary angioplasty in CTEPH - Rita Calé; Filipa Ferreira; Mariana Martinho; Sofia Alegria; Débora Repolho; Ana Rita Pereira; João Luz; Tiago Lobão; Patrícia Araújo; Sílvia Vitorino; Hélder Pereira; Daniel Caldeira (PLoS ONE, 2026)
Introduction Pulmonary endarterectomy (PEA) is the first-line treatment for chronic thromboembolic pulmonary hypertension (CTEPH), while balloon pulmonary angioplasty (BPA) is an established alternative for inoperable patients. Although both interventions improve resting pulmonary hemodynamics, the extent of long-term physiological recovery during exercise and the persistence of functional limitations remain incompletely characterized. Methods Prospective single-center registry (2017–2023) including 14 patients completing BPA (71 sessions) and 15 undergoing PEA, with median follow-up of 50 months (IQR 36–61). Clinical assessment included resting hemodynamics, invasive exercise right heart catheterization to derive the exercise slope of the mean pulmonary arterial pressure to cardiac output relashionship (mPAP/CO slope), and health-related quality of life (HRQOL) evaluated using the SF-36 questionnaire. Analyses were descriptive and focused on within-pathway changes over time. Results Both BPA and PEA significantly reduced mPAP (44.8 ± 12.4 → 26.1 ± 9.3 mmHg; 42.1 ± 12.9 → 22.6 ± 5.4 mmHg, both p < 0.001) and pulmonary vascular resistance (9.8 ± 4.6 → 3.0 ± 1.3 WU; 9.0 ± 5.4 → 2.9 ± 1.9 WU, both p < 0.001) at long term follow-up. Despite sustained improvements in resting hemodynamics, abnormal exercise pulmonary vascular responses persisted, with mean mPAP/CO slopes of 7.0 ± 5.6 mmHg/L/min after BPA and 4.0 ± 2.3 mmHg/L/min after PEA. Physical HRQOL remained impaired at long-term follow-up, with Physical Component Summary (PCS) scores below population norms in both pathways (44.4 ± 12.7 after BPA and 44.5 ± 7.3 after PEA). Conclusion BPA and PEA provide durable improvements in resting pulmonary hemodynamics; however, incomplete physiological recovery is common, with persistent exercise abnormalities and reduced physical quality of life at long-term follow-up.